(untitled) (Scientific journal of the Fergana State University, 2024)
The article talks about the representation of natural phenomena, in particular, the life of birds, the way of life and the characteristics, character, and behavior of people in fiction. In examples of folklore and written literature, attention is paid to the illumination of figurative and allegorical aspects of events in social life.